Using big data in cattle practice. Issue 9 (1st November 2018) - Hudson, Chris; Kaler, Jasmeet; Down, Peter
Abstract : The concept of big data, associated data sources and analytics is becoming increasingly talked about both in society as a whole and within the livestock industry. This article provides a clinician‐focused review of what big data means, how it is already influencing cattle farm and veterinary businesses, and where this may lead in the future. Cattle clinicians have a major role to play in making the best use of big data to improve animal health and efficiency.